The developmental support hypothesis: adaptive plasticity in neural development in response to cues of social support. (20th July 2020) - Snell-Rood, Emilie; Snell-Rood, Claire
Abstract : Across mammals, cues of developmental support, such as touching, licking or attentiveness, stimulate neural development, behavioural exploration and even overall body growth. Why should such fitness-related traits be so sensitive to developmental conditions? Here, we review what we term the 'developmental support hypothesis', a potential adaptive explanation of this plasticity. Neural development can be a costly process, in terms of time, energy and exposure. However, environmental variability may sometimes compromise parental care during this costly developmental period. We propose this environmental variation has led to the evolution of adaptive plasticity of neural and behavioural development in response to cues of developmental support, where neural development is stimulated in conditions that support associated costs. When parental care is compromised, offspring grow less and adopt a more resilient and stress-responsive strategy, improving their chances of survival in difficult conditions, similar to existing ideas on the adaptive value of early-life programming of stress. The developmental support hypothesis suggests new research directions, such as testing the adaptive value of reduced neural growth and metabolism in stressful conditions, and expanding the range of potential cues animals may attend to as indicators of developmental support. Considering evolutionary and ecologically appropriate cues of social support also has implications for promoting healthy neural development in humans. This article is part of the theme issue 'Life history and learning: how childhood, caregiving and old age shape cognition and culture in humans and other animals'.